2023
DOI: 10.3390/ijms24108641
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of microRNA-21-5p and microRNA-221-5p in Monocytes Increases the Risk of Developing Coronary Artery Disease

Abstract: MicroRNAs (miRs) regulate gene expression at the post-transcriptional level and are found to be present in monocytes. This study aimed to investigate miR-221-5p, miR-21-5p, and miR-155-5p, their expression in monocytes, and their role in coronary arterial disease (CAD). The study population comprised 110 subjects, and RT-qPCR was used to examine the miR-221-5p, miR-21-5p, and miR-155-5p expressions in monocytes. Results: the miR-21-5p (p = 0.001) and miR-221-5p (p < 0.001) expression levels were significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“… 47 Similarly, other research on patients with stable CAD has shown that elevating serum miRNA‐21 may contribute to the development of inflammatory pathways in the pathogenesis of CAD or may be related to the effects of inflammatory diseases on atherosclerosis and acute coronary syndrome. 48 In line with previous reviews, the present study indicates exo‐miRNA‐21‐3p has a significant positive correlation with hs‐CRP levels in CAD patients. Compared with exo‐miRNA‐21‐3p, exo‐miRNA‐21‐5p has a negative correlation with hs‐CRP levels, but this relationship is not significant.…”
Section: Discussionsupporting
confidence: 92%
“… 47 Similarly, other research on patients with stable CAD has shown that elevating serum miRNA‐21 may contribute to the development of inflammatory pathways in the pathogenesis of CAD or may be related to the effects of inflammatory diseases on atherosclerosis and acute coronary syndrome. 48 In line with previous reviews, the present study indicates exo‐miRNA‐21‐3p has a significant positive correlation with hs‐CRP levels in CAD patients. Compared with exo‐miRNA‐21‐3p, exo‐miRNA‐21‐5p has a negative correlation with hs‐CRP levels, but this relationship is not significant.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have been reported that EPAS1 [167], HOXA1 [734], TGM2 [114], CCND2 [191], MAP1B [204], EGFR (epidermal growth factor receptor) [198], NEDD4L [187], DCLK1 [196], hsa-mir-363-3p [738], SMAD4 [739], ATF3 [740], TBX5 [741] and CREB1 [742] increased the risk of inflammation development. Previous studies have reported that EPAS1 [486], HOXA1 [735], TGM2 [449], CCND2 [500], EGFR (epidermal growth factor receptor) [276], NEDD4L [496], DCLK1 [504], hsa-mir-363-3p [738], hsa-mir-21-5p [743], SMAD4 [744], ATF3 [745], TBX5 [746], SREBF1 [747], SMARCA4 [748] and CREB1 [749] were regulated in cardiovascular diseases. Studies reported that ERBB3 [255], TGM2 [223], CCND2 [274], EGFR (epidermal growth factor receptor) [276], hsa-mir-21-5p [750], ATF3 [751], SREBF1 [752], ARNT (aryl hydrocarbon receptor nuclear translocator) [753] and CREB1 [754] play important roles in diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Again, other studies that have been conducted on endothelial cells have shown the elevated expression of the 3p chain of this miR in patients having CAD [102,105]. Torres-Paz and colleagues also showed that miR-155-5p is downregulated in CAD patients [96]. According to the literature, the expression of miR-155-5p may have various effects depending on the stage of atherosclerotic plaque development.…”
Section: Fatty Acid Amide Hydrolase In Ldl Metabolism and The Effect ...mentioning
confidence: 97%
“…In a study by Torres-Paz and colleagues, it was shown that monocytes from patients who had coronary artery disease (CAD) significantly increased the expression of both miR-21-5p and miR-221-5p and also decreased the expression of miR-155-5p and NOS3 [96]. Moreover, only overexpression of miR-21-5p and miR-221-5p is closely associated with increased risk of coronary artery disease.…”
Section: Fatty Acid Amide Hydrolase In Ldl Metabolism and The Effect ...mentioning
confidence: 99%